Reflexive mapping exercise of services to support people experiencing or at risk of homelessness: a framework to promote health and social care integration. Issue 2 (3rd July 2021) - Rodriguez, Andrea; Arora, Garima; Beaton, Laura; Fernandes, Fernando; Freeman, Ruth
ABSTRACT: This article describes the process to create a framework to map services for people experiencing and/or at risk of becoming homeless. Using a participative and multi-agency approach the Reflexive Mapping Exercise (RME) was proposed to increase knowledge on what is available to address the health and social care needs of those experiencing homelessness and to encourage synergies between sectors addressing prevention and management of homelessness. Applied in the Scottish context of design and implementation of national and local policies, this framework identify gaps in service provision and can be a tool to improve integration and communication between services to support vulnerable groups. The RME results provided information of the current status of services in eight areas of care, combined with their spatial distribution. The analysis revealed an unequal distribution of services, with major focus on services addressing crisis periods of homelessness and less on prevention and sustainability out of homelessness. The REM has been informing the redesign of services of a local five years homelessness strategic plan (2016–2021) in a Scottish city, with high levels of deprivation, and can be used to create more integrated pathways to health and social care for people experiencing extreme social exclusion.